Frank and Lucky get schooled - Perkins, Lynne Rae (Greenwillow Books, An Imprint of HarperCollinsPublishers, 2016)
A boy and his dog learn about each other, go to school to learn more, then explore the world around them as they study science, geography and even foreign languages together.